PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 68 PALEMBANG - Rahayu, Sri; Widya Handayani; Henni Riyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Quantum Teaching learning model on the learning outcomes of class V students of SDN 68 Palembang with the TANDUR learning stages: Grow, Experience, Name, Demonstrate, Repeat and Celebrate. The type of research used in this study is Quantitative with the Quasi-Experimental method. The sample used in this study were students of class V.A and V.B SDN 68 Palembang with a total of 44 students. Data collection techniques in this study were tests, questionnaires, and documentation. The tests and questionnaires have been validated and declared valid and reliability tests have been carried out and declared reliable. This study, before conducting the hypothesis test, conducted a prerequisite test, namely the normality test and the homogeneity test and was declared normally and homogeneously distributed. The data analysis technique was carried out with the t-test, namely the Independent t-test which showed a significant value (2-tailed) of 0.006 <0.05. In addition, the results of the student response questionnaire to the learning model obtained results of 82.61% of students giving responses in the very positive category towards learning. As many as 17.39% of students are in the positive category. It can be concluded that there is a significant influence and Ha is accepted. This means that there is an influence of the Quantum Teaching learning model on the science learning outcomes of grade V students of SD Negeri 68 Palembang.